Phase‐Change Materials Based Nanoparticles for Controlled Hypoxia Modulation and Enhanced Phototherapy. (26th September 2019) - Zhang, Shichao; Li, Qinzhe; Yang, Nan; Shi, Yunhao; Ge, Wei; Wang, Wenjun; Huang, Wei; Song, Xuejiao; Dong, Xiaochen
Abstract: Tumor hypoxia strengthens tumor resistance to different therapies especially oxygen involved strategies, such as photodynamic therapy (PDT). Herein, the thermal responsive phase change materials (PCM) are utilized to coencapsulate ultrasmall manganese dioxide (sMnO2 ) and organic photosensitizer IR780 to obtain IR780‐sMnO2 ‐PCM nanoparticles for controlled tumor hypoxia modulation and enhanced phototherapy. The thermal responsive protective PCM layer can not only prevent IR780 from photodegradation, but also immediately release sMnO2 to decompose endogenous H2 O2 and generate enough oxygen for PDT under laser irradiation. Owing to the efficient accumulation of IR780‐sMnO2 ‐PCM nanoparticles in tumor under intravenous injection as revealed by both florescence imaging and photoacoustic imaging, the tumor hypoxia is greatly relieved. Furthermore, in vivo combined photothermal therapy (PTT) and PDT, IR780‐sMnO2 ‐PCM nanoparticles, compared to IR780‐PCM nanoparticles, exhibit better performance in inhibiting tumor growth. The results highlight the promise of IR780‐sMnO2 ‐PCM in controlled modulation of tumor hypoxia to overcome current limitations of cancer therapies. Abstract : The ultrasmall manganese dioxide (sMnO2 ) and IR780 are coencapsulated within phase change materials (PCM). The thermal responsive PCM layer in the obtained IR780‐sMnO2 ‐PCM can not only prevent IR780 from photodegradation, but also responsively release sMnO2 to decompose endogenous H2 O2 and generate enough oxygen for PDT under laser irradiation. Therefore, controlled tumor hypoxia modulation and enhanced phototherapy can be successfully achieved.